Challenges and controversies in the surgical management of Congenital Diaphragmatic Hernia - Mesas Burgos, Carmen; Perrone, Erin E.; Zahn, Katrin; Hedrick, Holly L. (Seminars in fetal & neonatal medicine, 2025)
Congenital diaphragmatic hernia (CDH) is a rare yet serious congenital condition marked by a diaphragmatic defect, pulmonary hypoplasia, and often pulmonary hypertension. While surgical repair is essential for survival, many controversies remain regarding its timing, approach, and techniques. Delayed repair after physiological stabilization is the current standard, though optimal timing varies. Earlier repair within 24-48 h may reduce hospital stay in some cases, while others benefit from extended stabilization. CDH patients on extracorporeal life support (ECLS) pose additional challenges, balancing bleeding risks against potential survival benefits when surgery is done on ECLS. Open surgical repair remains the gold standard, especially for large defects, with laparotomy preferred over thoracotomy. Minimally invasive surgery (MIS), although associated with better cosmetic and recovery outcomes, has higher recurrence rates and a steep learning curve. MIS is generally suited for smaller defects, though recent experience shows promising outcomes even in complex cases with patch repairs. Repair technique depends on defect size. Primary repair is preferred for small defects, while larger defects require synthetic or biological patches with emphasis on a tension-free repair for all defects. Synthetic patches offer strength but carry infection risks, whereas biological materials may lack durability. Muscle flap techniques offer an alternative, especially for recurrent or large defects. Recurrence remains a major concern, especially with large defects and patch repairs. Open reoperation is standard for recurrences, with MIS reserved for select cases. Prevention strategies include tension-free repair, appropriate patch choice, and meticulous technique. Emerging strategies, such as regenerative medicine, composite patches, and tissue engineering, show promise but are not yet widely available. Multicenter research, individualized care, and standardized reporting are essential to optimize outcomes and guide future innovations in CDH management.
Online verfügbar: 1. Juli 2025, Artikelversion: 16. Oktober 2025
Gesehen am 08.12.2025